A Role for CARM1-Mediated Histone H3 Arginine Methylation in Protecting Histone Acetylation by Releasing Corepressors from Chromatin - Wu, Jing; Cui, Nan; Wang, Rui; Li, Jiwen; Wong, Jiemin (PLOS ONE, 2012)
Arginine methylation broadly occurs in histones and has been linked to transcriptional regulation, cell cycle regulation and DNA repair. While numerous proteins (histone code effectors) that specifically recognize or read the methylated lysine residues in core histones have been identified, little is known for effectors specific for methylated arginines in histones. In this study, we attempted to identify effector(s) recognizing asymmetrically methylated R17 and R26 in H3, which are catalyzed by CARM1/PRMT4, through an unbiased biochemical approach. Although we have yet to identify such effector using this approach, we find that these modifications function cooperatively with histone acetylation to inhibit the binding of the nucleosome remodeling and deacetylase complex (NuRD) and TIF1 family corepressors to H3 tail in vitro. In support of this finding, we show that overexpression of CARM1 in 293 T cells leads to reduced association of NuRD with chromatin, whereas knockdown of CARM1 in HeLa cells leads to increased association of NuRD with chromatin and decreased level of histone acetylation. Furthermore, in the Carm1−/− MEF cells there is an increased association of NuRD and TIF1β with chromatin and a global decrease in histone acetylation. By chromatin immunoprecipitation assay, we show that overexpression of CARM1 results in reduced association of NuRD complex and TIF1β with an episomal reporter and that CARM1 is required in MEF cells for LPS-induced dissociation of NuRD from a NF-κb target gene. Taking together, our study provides evidence for a role of CARM1-mediated arginine methylation in regulation of histone acetylation and transcription: facilitating transcription by discharging corepressors from chromatin.